SARS-CoV-2 omicron (B.1.1.529)-related COVID-19 sequelae in vaccinated and unvaccinated patients with cancer: results from the OnCovid registry. Issue 4 (April 2023) - Cortellini, Alessio; Tabernero, Josep; Mukherjee, Uma; Salazar, Ramon; Sureda, Anna; Maluquer, Clara; Ferrante, Daniela; Bower, Mark; Sharkey, Rachel; Mirallas, Oriol; Plaja, Andrea; Cucurull, Marc; et al.
Summary: Background: COVID-19 sequelae can affect about 15% of patients with cancer who survive the acute phase of SARS-CoV-2 infection and can substantially impair their survival and continuity of oncological care. We aimed to investigate whether previous immunisation affects long-term sequelae in the context of evolving variants of concern of SARS-CoV-2. Methods: OnCovid is an active registry that includes patients aged 18 years or older from 37 institutions across Belgium, France, Germany, Italy, Spain, and the UK with a laboratory-confirmed diagnosis of COVID-19 and a history of solid or haematological malignancy, either active or in remission, followed up from COVID-19 diagnosis until death. We evaluated the prevalence of COVID-19 sequelae in patients who survived COVID-19 and underwent a formal clinical reassessment, categorising infection according to the date of diagnosis as the omicron (B.1.1.529) phase from Dec 15, 2021, to Jan 31, 2022; the alpha (B.1.1.7)–delta (B.1.617.2) phase from Dec 1, 2020, to Dec 14, 2021; and the pre-vaccination phase from Feb 27 to Nov 30, 2020. The prevalence of overall COVID-19 sequelae was compared according to SARS-CoV-2 immunisation status and in relation to post-COVID-19 survival and resumption of systemic anticancer therapy. This study is registered with ClinicalTrials.gov, NCT04393974 . Findings: At the follow-up update on June 20, 2022, 1909 eligible patients, evaluated after a median of 39 days (IQR 24–68) from COVID-19 diagnosis, were included (964 [50·7%] of 1902 patients with sex data were female and 938 [49·3%] were male). Overall, 317 (16·6%; 95% CI 14·8–18·5) of 1909 patients had at least one sequela from COVID-19 at the first oncological reassessment. The prevalence of COVID-19 sequelae was highest in the pre-vaccination phase (191 [19·1%; 95% CI 16·4–22·0] of 1000 patients). The prevalence was similar in the alpha–delta phase (110 [16·8%; 13·8–20·3] of 653 patients, p=0·24), but significantly lower in the omicron phase (16 [6·2%; 3·5–10·2] of 256 patients, p<0·0001). In the alpha–delta phase, 84 (18·3%; 95% CI 14·6–22·7) of 458 unvaccinated patients and three (9·4%; 1·9–27·3) of 32 unvaccinated patients in the omicron phase had sequelae. Patients who received a booster and those who received two vaccine doses had a significantly lower prevalence of overall COVID-19 sequelae than unvaccinated or partially vaccinated patients (ten [7·4%; 95% CI 3·5–13·5] of 136 boosted patients, 18 [9·8%; 5·8–15·5] of 183 patients who had two vaccine doses vs 277 [18·5%; 16·5–20·9] of 1489 unvaccinated patients, p=0·0001), respiratory sequelae (six [4·4%; 1·6–9·6], 11 [6·0%; 3·0–10·7] vs 148 [9·9%; 8·4–11·6], p=0·030), and prolonged fatigue (three [2·2%; 0·1–6·4], ten [5·4%; 2·6–10·0] vs 115 [7·7%; 6·3–9·3], p=0·037). Interpretation: Unvaccinated patients with cancer remain highly vulnerable to COVID-19 sequelae irrespective of viral strain. This study confirms the role of previous SARS-CoV-2 immunisation as an effective measure to protect patients from COVID-19 sequelae, disruption of therapy, and ensuing mortality. Funding: UK National Institute for Health and Care Research Imperial Biomedical Research Centre and the Cancer Treatment and Research Trust.